Pelatihan Kelas Expressive Writing untuk Santriwati Ma’had Tahfidz Al-Qur’an Darul Falah di Selangor Malaysia - Sorfina Rohim; Sefverly Aditya Noorinda; Erna Wijayanti (Devotion : Jurnal Pengabdian Psikologi, 2023)
The ability to manage emotions is essential for students. This service activity aims to provide psychoeducation to Ma'had Tahfidz Al-Qur'an Darul Falah Selangor Malaysia female students by organizing Expressive writing classes. Three stages are carried out: preparation, implementation, and evaluation. The service program chosen for this service is the expressive writing class. The interview service results show that expressive writing can make Ma'had Tahfidz Al-Qur'an Darul Falah female students love themselves more, be happier, and increase learning motivation. This service program can continue to be carried out for students in other Islamic boarding schools.